2017
DOI: 10.1002/lary.26659
|View full text |Cite
|
Sign up to set email alerts
|

Bone involvement: Histopathological evidence for endoscopic management of sinonasal inverted papilloma

Abstract: NA. Laryngoscope, 127:2703-2708, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 32 publications
1
27
0
1
Order By: Relevance
“…Some of their cases demonstrated that the bone had been eroded into pieces and certain parts had been invaded throughout. 14 We presume that in our cases containing a mismatch between radiologic and intraoperative findings, IP recurrence may be attributed to this phenomenon of intraosseous tumor growth instead of osteoneogenesis, at least in a part of the attachment zone. Also, 22% of specimens reported by Chiu et al contained an isolated nest of mucosa located deep in a crevice of bone underlying the IP pedicle.…”
Section: Discussionmentioning
confidence: 68%
“…Some of their cases demonstrated that the bone had been eroded into pieces and certain parts had been invaded throughout. 14 We presume that in our cases containing a mismatch between radiologic and intraoperative findings, IP recurrence may be attributed to this phenomenon of intraosseous tumor growth instead of osteoneogenesis, at least in a part of the attachment zone. Also, 22% of specimens reported by Chiu et al contained an isolated nest of mucosa located deep in a crevice of bone underlying the IP pedicle.…”
Section: Discussionmentioning
confidence: 68%
“…Still, our study did not correlate with post-operative specimens between sclerosis and origin of the tumor. Also, intra-lesional calcification is rare and non-specific; only one case presented with spotty calcified focus [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…10 The extent of surgery in this patient was decided based on the site of origin and area of mucosa involved by the lesion, with the aim being to dissect the involved mucosa in the subperiosteal plane and drill the underlying bone till normal bone is visible. 12,13 Endoscopic endonasal surgery is the gold standard and is preferred over external approach as there is a lower chance of recurrence, absence of a facial incision and reduced post operative pain and paraesthesia. 10 Endoscopic approach should not be used exclusively if a malignancy is present concomitantly with involvement of critical areas, if the inverted papilloma arises from the anterior wall or lateral recess of the frontal sinus or there is massive involvement of the mucosa of the frontal sinus and/or of a supra-orbital cell, or if the orbit is involved.…”
Section: Discussionmentioning
confidence: 99%